2018
DOI: 10.15575/jpib.v1i1.2071
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan Kualitas Puasa dan Kebahagiaan Santri Pondok Pesantren Al-Ihsan

Abstract: / AbstrakKeywords / Kata kunci

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 2 publications
0
6
0
2
Order By: Relevance
“…3 (Muhopilah et al, 2018) Fasting Quality, Happiness 150 students of Al-Ihsan Islamic Boarding School Cibiru Hilir, Bandung Regency.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…3 (Muhopilah et al, 2018) Fasting Quality, Happiness 150 students of Al-Ihsan Islamic Boarding School Cibiru Hilir, Bandung Regency.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequent research by Muhopilah et al, (2018) was conducted based on his initial study which found that fasting is one of the many worships that are often carried out by students at the pesantren Al-Ihsan, both mandatory and sunnah fasting. In addition to feeling thirsty and hungry, several respondents stated that when fasting they become more capable and have self-control over behaviors that can reduce or eliminate the reward of fasting.…”
Section: Articlementioning
confidence: 99%
See 1 more Smart Citation
“…The study also mentioned that when fasting, students controlled and prevented themselves from doing something destructive and bad; they were more patient and follow Allah's guidance and the direction mentioned in Quran and Hadith. The impact of those acts led to positive emotion, satisfaction, and happiness (Muhopilah et al, 2018). Fasting was recommended as the students' lifestyle in the boarding school.…”
Section: Positive Emotionmentioning
confidence: 99%
“…Bulan Ramadan menawarkan hal-hal positif di dalamnya. Adanya hal-hal positif yang menyenangkan dapat membuat seseorang merasakan kegembiraan (Muhopilah, Gamayanti, & Kurniadewi, 2018).…”
Section: Bulanunclassified